If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y(y + 2) = 0 Reorder the terms: 5y(2 + y) = 0 (2 * 5y + y * 5y) = 0 (10y + 5y2) = 0 Solving 10y + 5y2 = 0 Solving for variable 'y'. Factor out the Greatest Common Factor (GCF), '5y'. 5y(2 + y) = 0 Ignore the factor 5.Subproblem 1
Set the factor 'y' equal to zero and attempt to solve: Simplifying y = 0 Solving y = 0 Move all terms containing y to the left, all other terms to the right. Simplifying y = 0Subproblem 2
Set the factor '(2 + y)' equal to zero and attempt to solve: Simplifying 2 + y = 0 Solving 2 + y = 0 Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + y = 0 + -2 Combine like terms: 2 + -2 = 0 0 + y = 0 + -2 y = 0 + -2 Combine like terms: 0 + -2 = -2 y = -2 Simplifying y = -2Solution
y = {0, -2}
| 2tanx+7=3 | | 6+2x-5=6-3(2x-1) | | 10h-8h+h-3h+h=7 | | 5+3(x+4)=-(2x-1)-9 | | log[4](13*7)= | | 5r^2-10r-15=0 | | 2x^3+13x=8x^2 | | -17-55p=5(2+4p)+2p | | 20-2=38 | | -3(x-4)+2xy=xy-5x+xy-6 | | 2w^2-22w+48=0 | | 5(2)-2=38 | | (3g+2)(9g+5)=0 | | 5(10)-2=38 | | 300+12=960 | | 6-(x+9)=3-4x | | 10x-7y=-42 | | (d-6)(d-2)=0 | | 3(8)+7=25 | | 8(x+1)+3=7x+18 | | 3x-5(x+2)=12x+4 | | (v-7)(v-6)=0 | | 0.27t=129 | | 3+x=43 | | 96c^2+336c+294=0 | | 2(3)-5=17 | | v^2=-14+9v | | 5y-3=10y+4 | | 4k(3k+4)=0 | | 96c+336+284=0 | | =9(-6-x)-8x | | x^4+x^2-720=0 |